2018
DOI: 10.4067/s0717-95022018000301062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leucaena leucocephala (Lamk.) Shoot Tips Plus Young Leaf Extract Containing Mimosine on Reproductive System of Male Rats

Abstract: This study aimed to determine the mimosine level and examine the male reproductive toxicity effects of Leucaena leucocephala (LL) shoot tips plus young leaf extract. Mimosine level in LL extract was determined by thin layer chromatography before administration in animals. Male rats were divided into control and LL (1,500 mg/KgBW) groups (n = 6). After 60 days of experiment, serum sex hormones, sperm quality, and testicular histopathology were assayed and observed. Malondialdehyde (MDA) level and expressions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…These proteins have also been found to be localised in Leydig cells, Sertoli cells, spermatogonia, spermatocytes and spermatids, which are assumed to be important for spermatogenesis and androgen synthesis (Chaichun, Arun, Burawat, Kanla, & Iamsaard, ). The presence of TyrPho proteins in rat epididymal tissue and fluid has also been investigated (Sawatpanich et al, ), and improvements in testicular TyrPho protein changes have been associated with normal sperm and testosterone production (Burawat, Uabundit, Arun, Nualkaew, & Iamsaard, ; Iamsaard et al, , ; Iamsaard, Sukhorum, Sampannang, et al, ; Maneenin et al, ; Sampannang et al, ). Changes in TyrPho protein expression in the testis have been associated with stress‐related and diabetic conditions (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al, ; Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al, ; Sampannang, Arun, Burawat, Sukhorum, & Iamsaard, ; Sampannang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins have also been found to be localised in Leydig cells, Sertoli cells, spermatogonia, spermatocytes and spermatids, which are assumed to be important for spermatogenesis and androgen synthesis (Chaichun, Arun, Burawat, Kanla, & Iamsaard, ). The presence of TyrPho proteins in rat epididymal tissue and fluid has also been investigated (Sawatpanich et al, ), and improvements in testicular TyrPho protein changes have been associated with normal sperm and testosterone production (Burawat, Uabundit, Arun, Nualkaew, & Iamsaard, ; Iamsaard et al, , ; Iamsaard, Sukhorum, Sampannang, et al, ; Maneenin et al, ; Sampannang et al, ). Changes in TyrPho protein expression in the testis have been associated with stress‐related and diabetic conditions (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al, ; Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al, ; Sampannang, Arun, Burawat, Sukhorum, & Iamsaard, ; Sampannang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in TyrPho protein expression in the testis have been associated with stress‐related and diabetic conditions (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al, ; Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al, ; Sampannang, Arun, Burawat, Sukhorum, & Iamsaard, ; Sampannang et al, ). Moreover, some anticancer drugs, such as VPA, methotrexate, ketoconazole and mimosine, have been shown to alter the patterns of TyrPho proteins in the testis and epididymis (Burawat et al, ; Iamsaard et al, , , ; Maneenin et al, ; Sawatpanich et al, ; Sukhorum & Iamsaard, ). Although the toxic effects of VPA on some male reproductive organs (especially the testis and epididymis) have been demonstrated, its effect on the seminal vesicle, the biggest accessory organ that produces essential seminal plasma nutrients, has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…By colorimetric determination, mimosine level in LL leaves grown in North, Thailand was 4.4 % dry weight of total proteins (Chanchay & Poosaran). Our research group has investigated the level of mimosine content in aqueous crude extract of LL shoot tips plus young leaves cultured in Northeastern, Thailand by using Thin Layer Chromatography with method validation for the first time and we found that its mimosine level was 17.35 % dry crude extract (Burawat, 2017). Previous study has demonstrated that LL crude extract could damage male reproductive system (Burawat et al).…”
Section: Discussionmentioning
confidence: 87%
“…Mimosine (MiMo) has been proven to have activities against many cancers, cell divisions, cell proliferations and differentiations (Wang et al, 1995;Hughes & Cook;Krude). Indeed, MiMo is a toxic substance in Leucaena leucocephala (LL) (Zayed et al, 2014;Burawat, 2017;Burawat et al, 2016Burawat et al, , 2018. By using Thin Layer Chromatography (TLC) with method validation, Burawat et al (2018) have demonstrated for the first time that MiMo levels in aqueous crude extract of LL shoot tips plus young leaves cultured in Northeastern, Thailand were approximately 17.35 % dry crude extract.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MiMo is a toxic substance in Leucaena leucocephala (LL) (Zayed et al, 2014;Burawat, 2017;Burawat et al, 2016Burawat et al, , 2018. By using Thin Layer Chromatography (TLC) with method validation, Burawat et al (2018) have demonstrated for the first time that MiMo levels in aqueous crude extract of LL shoot tips plus young leaves cultured in Northeastern, Thailand were approximately 17.35 % dry crude extract. Particularly, both aqueous crude extract of LL shoot tips plus young leaves and purified MiMo have previously reported to have adverse effects on male reproductive mouse organs such as testis, epididymis, and seminal vesicle (Burawat et al, 2018;Kanla et al).…”
Section: Discussionmentioning
confidence: 99%